The concept of rights, its impact and importance on women in contemporary societies : a legal overview - Kunju Pillai Laxman, Lekha (Faculty of Management and Human Resource Development, 2003)
This article provides a legal over view of women's right in contemporary societies as well as plausible explanations on why violations of women's rights are merely given fleeting interests by global communities around the world. It is proposed in the article that the root cause of violations and discrimination, which continue to be pervasive components of many women's lives, can be traced to the concept of rights in general and how it is formulated in accordance to the western perspective. Rousseau's idea of social contract' is used to argue why there has been a breach in the said contract when societies and their legal systems fail to protect the rights and overall welfare of women. The article identifies key areas in which women have experienced violations of their rights and the root cause why such violations continue to occur in many societies throughout the world. This article concludes with a brief discussion on the importance of empowering women and recommends the adoption of the Convention on the Elimination of all forms of Discrimination against women into their respective national legal provisions.